Analisis Perkembangan Emosional Anak Kelompok B Saat Kegiatan Drumband Di Tk Aisyiyah Bustanul Athfal 24 Gresik - Nisriinaa Salmaa; Rr. Agustin Lilawati; Ayunda Sayyidatul Ifadah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to determine the emotional development of group B during drum band activities at Aisyiyah Bustanul Athfal 24 Gresik Kindergarten. This study used variables in the form of drumband learning in group B children, emotional development of group B children. Qualitative descriptive research respondents with case studies, observations, data analysis, interviews, and documentation. The results of the study showed that in Aisyiyah Bustanul Athfal 24 Gresik Kindergarten in the emotional development of children during drumband learning, the researcher observed that during activities at the beginning of learning until the end of learning, practice habits were carried out once a week on Monday at 10.00 - 11.00 WIB, if it was close to the time for the drum band competition, the practice was held almost 3 times a week at a predetermined time school. In playing drumband, children's emotional development is a great opportunity in that development. With the right support, children not only enjoy drumband playing activities but also grow individual personalities that are more confident, disciplined, and able to manage the emotions of group B children well.